1994
DOI: 10.1002/ijc.2910590615
|View full text |Cite
|
Sign up to set email alerts
|

Effective anti‐metastatic melanoma vaccination with tumor cells transfected with MHC genes and/or infected with newcastle disease virus (NDV)

Abstract: The therapeutic efficacy of active immunization with B16-F10.9 melanoma cells transfected with syngeneic major histocompatibility complex (MHC) class-I genes, modified by infection with Newcastle Disease virus (NDV) or modified by both treatments, was compared. B16-F10.9 tumor-bearing mice were treated at various stages of tumor growth and metastasis with irradiated, modified tumor-cell vaccines. Irradiated tumor cells and H-2Db transfectants did not stimulate anti-tumor immunity while H-2Kb transfectants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…39 Similar results were obtained by von Hoegen et al, 16,17 who characterized the effects of NDV infection in a murine model using the highly metastatic murine lymphoma line ESb injected in immunocompetent syngenic DBA/2 mice. They demonstrated that spleen cells from mice immunized with NDV-infected ESb cells contain an enhanced immune capacity in both CD4 ϩ and CD8 ϩ T-cell compartments.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…39 Similar results were obtained by von Hoegen et al, 16,17 who characterized the effects of NDV infection in a murine model using the highly metastatic murine lymphoma line ESb injected in immunocompetent syngenic DBA/2 mice. They demonstrated that spleen cells from mice immunized with NDV-infected ESb cells contain an enhanced immune capacity in both CD4 ϩ and CD8 ϩ T-cell compartments.…”
Section: Discussionsupporting
confidence: 81%
“…This is in accordance with the finding that NDV infection efficiently prevents the growth and micrometastasis of established B16 melanoma in immunocompetent mice only if these are MHC-matched. 39 Furthermore, lymphocytes play an essential role in NDV-mediated tumor lysis in vivo, because depletion of CD4 ϩ , CD8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, herpes simplex virus 17 and vesicular stomatitis virus 8 appear to exert antitumoral immune responses in addition to their oncolytical effect. In a similar manner, herpes simplex virus, 17 vesicular stomatitis virus 8 and Newcastle disease virus 29 -infected tumor cells have been reported to activate antitumoral immunity. Previous studies with replication-competent adenovirus-infected carrier-cell systems have reported the use of wild-type HAd5 adenovirus-infected MDA-MG-231 cells 30 and also of granulocyte-macrophage colonystimulating factor-expressing HAd5 loaded into A549 and 293 cells.…”
Section: Discussionmentioning
confidence: 87%
“…12 Postoperative vaccination with NDV-modified autologous tumor cell vaccine (ATV-NDV) was effective in vivo in various animal tumor models to prevent metastatic spread and to increase survival. 13,14 The mechanism of the immunopotentiating effect of this virus was analyzed in detail. [15][16][17] Since 1988, a comparable ATV-NDV was developed for clinical application.…”
mentioning
confidence: 99%